Entrepreneurship Education: A Veritable Tool for Employment Generation Among Faculty of Education Graduates, Nnamdi Azikiwe University, Awka, Nigeria. - Chinyere, Nwankwo, Madeleine; Nnajiofor, F. N. (Advances in Social Sciences Research Journal, 2021)
The study examined entrepreneurship education (EE) as a veritable tool for employment generation among Nigerian graduates. A survey research design was used for the study. The population of the study was all the 987 final year students of faculty of education 2019/2020 academic session in Nnamdi Azikiwe University, Awka, Nigeria. Stratified sampling technique was used to select 10 % of students in each department, making a total of 99 students who constituted the study sample. The instrument for data collection for the study was a 31-item researcher-constructed questionnaire divided into four clusters. The instrument was validated by experts and tested for reliability using Cronbach’s alpha which yielded a reliability index of 0.71. Mean and standard deviation were used to analyze the Data. The findings of the study showed among others that the method and techniques of teaching EE in Nigerian universities is not adequate. Based on the findings, recommendations were made which included among others that government should strive to adequately fund EE and provide functional EE centers in every Nigerian University.